The impact of COVID‐19 on Italian adolescents' sleep and its association with psychological factors. (13th July 2022) - Bacaro, Valeria; Meneo, Debora; Curati, Sara; Buonanno, Carlo; De Bartolo, Paola; Riemann, Dieter; Mancini, Francesco; Martoni, Monica; Baglioni, Chiara
SUMMARY: Insomnia and circadian dysregulation during adolescence represent important risk factors for emotional and psychological problems. Recent studies have shown that the coronavirus disease 2019 (COVID‐19) pandemic has been linked to a high prevalence of behavioural sleep problems in the general population. This study aimed to provide two pictures of two different time points of the pandemic regarding the prevalence of sleep problems in adolescents and their association with psychological health variables. Two different independent large samples of Italian adolescents aged 13–17 years were recruited at two pandemic time points. A total of 1, 146 adolescents at Time 1 (T1; April 2020) and 1, 406 at Time 2 (T2; April 2021) took part in the study. Measures of insomnia symptoms, sleep hygiene, chronotype, psychological distress and emotion regulation were collected. Prevalence of insomnia was 12.13% at T1 and 23.19% at T2. Furthermore, high levels of poor sleep habits (late bedtime, poor sleep hygiene, use of electronic devices at bedtime) were also detected at both time points. Insomnia symptoms strongly correlated with poor sleep hygiene, higher psychological distress, and emotional suppression at both time points. Results highlighted an alarming picture for two large samples at two different time points of the pandemic that showed a potential negative impact of the COVID‐19 pandemic, in both the first outbreak and in the later phase of the pandemic, on sleep habits, psychological distress and insomnia symptoms in adolescents. This strongly suggests the need for monitoring these variables and their interaction in the post‐pandemic period and to develop and promote interventions for insomnia and circadian disturbances during adolescence.